(untitled) (Voice of Teacher, 2022)
Intimate partner Violence is one of the most widespread and may take place in any age, family, community, cultural, ethnical or religious group and religions in different forms and disparately impacts their life. Violence against Women (VAW) by their husband is one of the most common forms of violence in our society. Therefore, cross-sectional survey was conducted among female students studying in bachelors and masters level at Baneshwor Campus using structured and semi-structured questionnaires. A total of 215 participants were randomly selected and data were collected from the 1 December 2020 to 30 January 2021. One-thirds of the respondents were married. Married participants reported about their violence experience perpetrated by their husbands. The prevalence of emotional violence 40% was higher than physical 33% and sexual violence20%. Women with land ownership, employed, members of community groups and those who were married to husbands with the higher level of education were less likely to experience physical violence. Women who did not own land (OR=2.92), unemployed (OR=1.21) were more likely to experience violence than those who owned land and were employed. Similarly, lower level of husband’s education (OR=3.35) and unskilled jobs(OR=1.56) were associated with the higher occurrence of violence compared to their husbands having university level of education and government job or working abroad. Women experienced violence by their husband is common among educated girls.